2010
DOI: 10.1016/j.quascirev.2009.09.002
|View full text |Cite
|
Sign up to set email alerts
|

A major glacial-interglacial change in aeolian dust composition inferred from Rare Earth Elements in Antarctic ice

Abstract: a b s t r a c tWe present the first Rare Earth Elements (REE) concentration record determined in 294 sections of an Antarctic ice core (EPICA Dome C), covering a period from 2.9 to 33.7 kyr BP. REE allow a detailed quantitative evaluation of aeolian dust composition because of the large number of variables (i.e. 14 elements). REE concentrations match the particulate dust concentration profile over this period and show a homogeneous crustal-like composition during the last glacial stage (LGS), with only a sligh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
75
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 92 publications
(84 citation statements)
references
References 47 publications
8
75
0
Order By: Relevance
“…1a,b) follow well-defined glacialinterglacial variations, with the lowest concentrations during the Holocene MIS 1 (14 samples, average 0.36 pg Pb/g, 10.2 pg Ba/g) and Eemian MIS 5.5 (4 samples, average 0.41 pg Pb/g, 11.2 pg Ba/g) and the highest concentrations during the Last Glacial Maximum (LGM) MIS 2 (10 samples, average 13.4 pg Pb/g, 278 pg Ba/g). The data are in good agreement with LGM/Holocene REE concentrations ratios found in the EDC ice core (Gabrielli et al, 2010). A comparison of Pb and Ba concentrations to dD demonstrates the well-reported nonlinear sensitivity of dust fallout to climate , in which low Pb and Ba concentrations are observed at warmer temperatures (dD > À435&) while Pb and Ba concentrations increase steeply at colder temperatures (dD < À435&).…”
Section: Edc Ice Samplessupporting
confidence: 83%
“…1a,b) follow well-defined glacialinterglacial variations, with the lowest concentrations during the Holocene MIS 1 (14 samples, average 0.36 pg Pb/g, 10.2 pg Ba/g) and Eemian MIS 5.5 (4 samples, average 0.41 pg Pb/g, 11.2 pg Ba/g) and the highest concentrations during the Last Glacial Maximum (LGM) MIS 2 (10 samples, average 13.4 pg Pb/g, 278 pg Ba/g). The data are in good agreement with LGM/Holocene REE concentrations ratios found in the EDC ice core (Gabrielli et al, 2010). A comparison of Pb and Ba concentrations to dD demonstrates the well-reported nonlinear sensitivity of dust fallout to climate , in which low Pb and Ba concentrations are observed at warmer temperatures (dD > À435&) while Pb and Ba concentrations increase steeply at colder temperatures (dD < À435&).…”
Section: Edc Ice Samplessupporting
confidence: 83%
“…5). All our ice floats and snow exhibited MREE enrichment, which could be from Patagonian origin because this pattern resembles those from volcanic rocks sampled in that region (Gaiero et al 2004) and/or those shown by South American dust (Gabrielli et al 2010).…”
Section: Rees As Tracers Of Gmw-derived Trace Elementsmentioning
confidence: 56%
“…Grousset and Biscaye 2005). More recently, new isotopic and elemental composition systems (e.g., Pb, Li, He isotopes) have been utilized to fingerprint geochemically the dust (Vallelonga et al 2010;Gabrielli et al 2010;Marino et al 2008;Winckler and Fischer 2006;Siggaard-Andersen et al 2007); yet, geochemical data There is increasing consensus that dust deposited in Antarctica during interglacial time periods is derived from a mixture of dust sources rather than a single source. Potential sources include different regions within southern South America and other sources like AUS (Revel-Rolland et al 2006;Delmonte et al 2007) or possibly the PunaAltiplano area (Delmonte et al 2008a;Gaiero 2008), and match the limited data on the isotopic signature of interglacial dust from the studied ice cores.…”
Section: Comparing Model Results With Observations: Current Climatementioning
confidence: 99%